1997
DOI: 10.1007/bf01007832
|View full text |Cite
|
Sign up to set email alerts
|

Application of HELP in nonarteritic anterior ischemic optic neuropathy: A prospective, randomized, controlled study

Abstract: The HELP system seems to be safe and more effective than hemodilution in improving the hemorheological and the functional situation in NAION and could be a promising regimen in the treatment of NAION.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…In a previous work, Haas et al [29] demonstrated that treatment with LDL apheresis (HELP system) can improve the visual parameters in patients affected by NAION, obtaining more significant results than in the control group treated with hemodilution. Instead, visual acuity, expressed in logMAR units, did not show significant differences between the group treated with apheresis and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, Haas et al [29] demonstrated that treatment with LDL apheresis (HELP system) can improve the visual parameters in patients affected by NAION, obtaining more significant results than in the control group treated with hemodilution. Instead, visual acuity, expressed in logMAR units, did not show significant differences between the group treated with apheresis and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The only randomized control study for the treatment of NAION was the IONDT (Ischemic Optic Neuropathy Decompression Trial) [4] which suggested that optic nerve decompression surgery for NAION patients is ineffective, and may even be harmful. Other studies explored the role of aspirin [5-7], vasodilators [8], heparin-induced extracorporeal LDL/fibrinogen precipitation (HELP) [9], hyperbaric oxygen [10], diphenylhydantoin [11], norepinephrine [12], levodopa [13], topical brimonidine [14,15], intravitreal bevacizumab [16,17] and systemic corticosteroids [18-20]. Recently Prokosch et al showed that adding the corticosteroid floucortolone to their standard treatment (intravenous and per os pentoxifylline for one week and then per os for a further 6 months) slightly improves the short and long term visual acuity (VA) in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the hemodilution group, visual acuity increased in 33.4%, remained stable in 42.8% and worsened in 23.8%. There was mild, but statistically significant (p < 0.01) improvement in the mean sensitivity of visual fields in the HELP group that was not seen in the hemodilution group [39].…”
Section: Vasodilatorsmentioning
confidence: 95%
“…It is theorized that the precipitation of these substances may improve the circulatory milieu to which the optic nerve at risk for NAION is exposed. In a prospective, randomized, controlled study over a period of 3 months, 40 patients with acute NAION and symptom onset within 2 weeks were randomly assigned to either HELP or hemodilution therapy to determine the efficacy of these two treatments on visual acuity and fields [39]. There was no difference in visual acuity between the two groups (p = 0.48).…”
Section: Vasodilatorsmentioning
confidence: 98%